-6y-7=-37

Simple and best practice solution for -6y-7=-37 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6y-7=-37 equation:


Simplifying
-6y + -7 = -37

Reorder the terms:
-7 + -6y = -37

Solving
-7 + -6y = -37

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + -6y = -37 + 7

Combine like terms: -7 + 7 = 0
0 + -6y = -37 + 7
-6y = -37 + 7

Combine like terms: -37 + 7 = -30
-6y = -30

Divide each side by '-6'.
y = 5

Simplifying
y = 5

See similar equations:

| 6x-3+x=5(1+x)-6 | | 6x-1=13-x | | 5x-12=4x+29 | | ln(x)=3.06 | | 3x-4-x=4 | | 8a-b-3a-2b= | | 25=1.2x+9 | | -37=-6-7 | | x+(y+3)=13 | | 5x-14=19-6x | | v=17*2*1 | | (3x)w=30 | | 2+6x+x=30 | | 2.1x-1=x+11.1 | | X^2-4x-500=0 | | 21=-x | | x+(2x+15)+(x+15)=180 | | -4+4x-5x=1 | | 6X-11=8X+10 | | .2x+9+.8x=-11 | | 12m+6n-5m+8n= | | k=v+29 | | 4(x+9)+3=9x-5(x-3) | | -5(x+4)+98=28+10 | | 10a=7 | | 2y+12=-2 | | -5x+10+4x=0 | | 2a+3b-c=18 | | 3x=-2x^2 | | 2X+94=10X-10 | | -3x-(-4)=3x+10 | | 123456789012345678901234567890+98765432109876543210987654321= 222222221122222222112222222211 |

Equations solver categories